KORELASI ANTARA DERAJAT PENYAKIT SIROSIS HATI BERDASARKAN KLASIFIKASI CHILD-TURCOTTE-PUGH DENGAN KONSENTRASI TROMBOPOIETIN SERUM - Juliana, I Made; Wibawa, I Dewa Nyoman (journal of internal medicine, 2012)
Thrombocytopenia is one of the most frequent haematological abnormalities in patients with liver cirrhosis. It is generally considered to be due to pooling and destruction of the platelets in enlarged spleen which was defined as hypersplenism. Portal decompression procedures, either by surgical shunts or transjugular intrahepatic portosystemic shunt (TIPS) have not led to a consistent rise in thrombocytes count. With the discovery of the lineage specific cytokine thrombopoietin (TPO) in 1994, the missing link between hepatocelular function and thrombopoiesis was found. TPO is predominantly produced by the liver and constitutively expressed by the hepatocytes. In liver cirrhosis, the damaged of liver cells reduced TPO production. This leads to reduce thrombopoiesis in the bone marrow and consquently causes thrombocytopenia. However, these two pathogeneses were still remained controversial results in previous study abroad. The aim of this study was to determine the correlation between disease severity of liver cirrhosis based on Child-Turcotte-Pugh classification and serum thrombopoietin concentration. An analytic cross sectional study had been conducted among liver cirrhotic patients in Sanglah Hospital Denpasar. The subject were adult liver cirrhotic patients that were not on upper or lower gastro-intestinal tract bleeding, septic codition/septic shock, without history of taking antithrombocytic drugs or received platelets transfusion in last two weeks, and no history of thrombocytopenia due to primary haematologic disorders. Statistical analysis was done by Spearman’s test and multivariate linier regression model, with significant level p < 0,05. The number of subjects were 39 liver cirrhotic patients consist of 28 (71.8%) men and 11 (28.2%) women. The median of age was 53 (25 – 68) years. We found subjetcs with Child-Turcotte-Pugh class A 3 (7.7%), B 18 (46.2%) and C 18 (46.2%) respectively with the median of Child-Turcotte-Pugh score was 9 (6 – 14). The range of serum TPO concentration was 1.10 – 224.60 pg/ml, median of serum TPO was 40.60 pg/ml. The median of thrombocyte was 103 x 103/L with range of 30 – 729 x 103/L. Liver cirrhotic patients with thrombocytopenia were 29 (74.4%), 41.0% of them with moderate thromboytopenia. We found negative correlation between Child-Turcotte-Pugh score and serum TPO concentration ( r = - 0.319; p = 0.048) but there was no correlation between Child-Turcotte-Pugh class and TPO concentration. (r = -0.303; p = 0.061). We found significant positif correlation between thrombocyte count and serum TPO concentration also (r = 0.354; p = 0.027). Based on multivariate linier regression model, we did not find significant association between TPO concentration and Child-Turcotte-Pugh score (p = 0.153) or thrombocyte count (p = 0.208), respectively. Conclusion: there was no correlation between disease severity of liver cirrhosis based on Child-Turcotte-Pugh classification and serum thrombopoietin concentration.
Keywords: Child-Turcotte-Pugh score, Child-Turcotte-Pugh class, serum TPO concentration, thrombocyte count